The infinite moment of us - Myracle, Lauren, 1969- (New York : Amulet Books, 2013)
As high school graduation nears, Wren Gray is surprised to connect with gentle Charlie Parker, a boy with a troubled past who has loved her for years, while she considers displeasing her parents for the first time and changing the plans for her future.
Keywords: Dating (Social customs) -- Fiction; Love -- Fiction; Family life -- Georgia -- Fiction; Assertiveness (Psychology) -- Fiction; JUVENILE FICTION / Social Issues / Dating & Sex; JUVENILE FICTION / Social Issues / Friendship; JUVENILE FICTION / Girls & Women; Atlanta (Ga.) -- Fiction